A cross-sectional study on the tea consumption effects of ankle–brachial index. (April 2023) - Gu, Lishuang; Liu, Xuemei; Wu, Shouling; Chu, Kaiyun; Bao, Jing-jing
Objectives: This thesis aims to explore the relationship between tea consumption and ankle–brachial index (ABI) and further studies the relationship between tea consumption and lower extremity atherosclerosis. Methods: This is a cross-sectional, epidemiological survey of 17, 373 subjects selected from the staff of Kailuan Group who had come to Kailuan General Hospital for a health examination from January 2016 to December 2017. Tea consumption was obtained by questionnaires. ABI was measured using an automated analyzer. The other data, such as age, gender, body mass index (BMI), and so on, was collected on the same day of the health examination results. The relationship between tea drinking habits and ABI was studied using logistic regression and multivariate linear regression analysis. Results: Among the 17, 373 analyzed subjects, the difference in age, gender, BMI, heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), uric acid (UA), C-reactive protein (CRP), fasting blood-glucose (Fbg), and ABI was statistically significant in the tea-drinking group and the nontea-drinking group ( p < 0.05). Multiple logistic regression models revealed that tea consumption was a positive predictor for ABI (odds ratio (OR) = 0.782, confidence interval (CI), 0.615–0.994) ( p < 0.05). Multivariate linear regression analysis of the ABI value showed that frequent tea-drinking has a positive correlation with the ABI value ( p < 0.05). Conclusions: The higher tea consumption is significantly associated with higher ABI which means less risk for lower extremity atherosclerosis.